Unmet Needs for Information and Support Among Military Caregivers. Issue 11 (8th May 2019) - Rylee, Tina L; Sarkar, Sayantani; Reed, Sarah C; Rafizadeh, Elbina; Bell, Janice F
Abstract: Introduction: In the United States, there are 5.5 million military caregivers, defined as family members, friends, or other acquaintances who provide essential care and support to current or former military service members. This study describes the prevalence and predictors of unmet information and support needs in this unique group of caregivers. Until recently, little research has focused on military caregivers. In 2014, a comprehensive RAND report underscored the specific challenges experienced by military caregivers including greater physical, financial, and emotional strain when compared with civilian caregivers. Of note, compared to civilian caregivers, military caregivers provide care and support for care recipients who are more likely to have complex illness. While this recent research improved our understanding of the increased burden associated with military caregiving, it also identified gaps for future work, including the need for additional studies to better understand unmet information and support needs to inform future interventions. The current study was designed to address this gap. Materials and Methods: We examined data collected in the Caregiving in the U.S. Survey, a cross-sectional online survey fielded in 2014, by the National Alliance for Caregiving and the American Association of Retired Persons (AARP) for primary caregivers who had been in the role for at least six months. Four outcomes representing unmet caregiver needs were examined measuring caregiver report of needing more help or information to: (1) keep the care recipient safe at home; (2) manage challenging behaviors such as wandering; (3) manage their own emotional and physical stress; and (4) make end-of-life decisions. Survey-weighted logistic regression was used to test associations between military caregiver status (military/civilian) and unmet needs while controlling for key socio-demographic, caregiving and care recipient health variables, with nationally generalizable results. Results: Compared to their civilian counterparts, military caregivers had significantly higher odds of reporting need for information or support to make end-of-life decisions (OR = 2.22; 95% CI: 1.24, 3.97; p = 0.01) and marginally higher odds of reporting need for more information or support to manage physical and emotional stress (OR = 1.64; 95% CI: 0.93, 2.88; p = 0.08). In contrast, military caregivers had significantly lower odds of reporting need for more information or support to keep the care recipient safe compared to civilian caregivers (OR = 0.54; 95% CI: 0.30, 0.95; p = 0.03). Reports of unmet needs related to managing challenging behaviors were similar between military and civilian caregivers. Conclusions: Needs for information and support differ for civilian and military caregivers and may reflect direct or indirect impacts on caregivers arising from differences in TRICARE and Veterans Affairs health insurance coverage and related benefits, services and systems or access to resources that address the unique needs of military populations. Future research is needed to better understand the unique concerns of military caregivers and inform interventions that support end-of-life care decision-making for military service members and their caregivers.